LITERAL READING - Ferdiyanto, Feri (Insight Mediatama, 2022)
"Literal Reading" is a comprehensive textbook designed to enhance students' reading skills through a structured and interactive approach. Divided into twelve chapters, the book includes reading texts, exercises, quizzes, glossaries, and pronunciation guides. Each chapter focuses on essential reading strategies, such as identifying main ideas and details, skimming, scanning, predicting, previewing, using context clues, making inferences, and taking notes. These techniques are crucial for academic success and personal growth, promoting critical thinking and analytical skills. "Literal Reading" provides a holistic learning experience, encouraging active engagement and ensuring students comprehend, retain, and apply their knowledge effectively.